Electrochemical assessment of concrete ternary inhibitors used in retarding corrosion of steel reinforcement - Abdulrahman, A.; Ismail, Mohamed (Asian Research Publishing Network (A R P N), 2014)
Corrosion of steel reinforcement in concrete is generally considered as an electrochemical process which reduces the service life of a structure exposed to chloride ions attack. Therefore, laboratory experiments were performed in order to ascertain the effectiveness and sustainability of ternary inhibitors (calcium nitrite, ethanolamine and eco-friendly green Bambusa Arundinacea) in protecting steel reinforcement in concrete from corrosion attack due to chloride. Concrete mix was designed to be 30MPa with 0.45 and 0.65 W/C ratios. Inhibitors additions were 2% and 4% by weight of cement. The specimens were subjected to various durability corrosion test (using; electrochemical impedance spectroscopy (EIS)) for 360 days. The results showed that Bambusa arundinacea has exhibited lowest corrosion rate, highest concrete resistance and highest polarization resistance (Rp) values for the period of exposure, compared to calcium nitrite and ethanolamine. Bambusa arundinacea may be considered a better substitute for nitrite and amine- based corrosion inhibiting admixtures for durable concrete structures due to its viability, versatility and eco-friendliness. © 2006-2014 Asian Research Publishing Network (ARPN).